Some Impressions of the Permanent Appellate Judges: 1958–2002 - Richardson, Ivor LM (Victoria University of Wellington Law Review, 2016)
In this article, the late Rt Hon Sir Ivor Richardson provides personal insight into the inner workings of the Court of Appeal and reflections on each of the judges appointed since its inception as a permanent appellate court in 1958 until 2002. Drawing on his vast experience as an advocate, as a judge and as a President of the Court of Appeal, Sir Ivor canvasses the Court as led by various judges: Gresson, North, Turner, McCarthy, Richmond, Woodhouse, Cooke and Sir Ivor himself. Sir Ivor retired as President of the Court of Appeal in 2002 after 25 years in judicial office. He wrote the bulk of the paper that forms this article in 2009, but it remained unfinished at the time of his death in 2014. The paper is reproduced here largely as it was written; only minor edits have been made for clarity.